1999
DOI: 10.1038/sj.bjc.6690766
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide sensitivity is associated with low level of glutathione in cancer cells

Abstract: Arsenic trioxide (As 2 O 3 ) is a novel anticancer agent, which has been found to induce remission in acute promyelocytic leukaemic patients following daily intravenous administration. The therapeutic value of As 2 O 3 in other cancers is still largely unknown. Cytotoxic tests in a panel of cancer cell lines showed that bladder cancer, acute promyelocytic leukaemic and gastrointestinal cancer cells were the most sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 11 publications
6
79
1
Order By: Relevance
“…In fact, production of ROS can be suppressed by Bcl-x L and inhibition of glutathione synthesis by BSO enhanced arsenite induced necrotic cell demise as reported previously in arsenite-induced apoptosis Kitamura et al, 2000). Functional data corroborate that generation of ROS is a key feature of arsenite-mediated cell death (Wang et al, 1996;Chen et al, 1998;Jing et al, 1999;Yang et al, 1999). Oxidative stress induces cell death through mitochondria, where the pursuit of an apoptotic or a necrotic pathway depends on the strength of the insult and the availability of functional caspases (Fernandes and Cotter, 1994;Fiers et al, 1999).…”
Section: Discussionsupporting
confidence: 68%
“…In fact, production of ROS can be suppressed by Bcl-x L and inhibition of glutathione synthesis by BSO enhanced arsenite induced necrotic cell demise as reported previously in arsenite-induced apoptosis Kitamura et al, 2000). Functional data corroborate that generation of ROS is a key feature of arsenite-mediated cell death (Wang et al, 1996;Chen et al, 1998;Jing et al, 1999;Yang et al, 1999). Oxidative stress induces cell death through mitochondria, where the pursuit of an apoptotic or a necrotic pathway depends on the strength of the insult and the availability of functional caspases (Fernandes and Cotter, 1994;Fiers et al, 1999).…”
Section: Discussionsupporting
confidence: 68%
“…Several in vitro experiments have already examined the efficacy of the combined treatment with As 2 O 3 plus BSO, although the approach is experimental, not therapeutic. 13,18,19 However, to our knowledge, this is the first in vivo study that investigated the combination therapy with As 2 O 3 plus BSO. Our in vivo study showed that this combination induced tumor growth inhibition in both primary and metastatic lesions, and that this combination therapy prolonged survival rate significantly compared with the control or As 2 O 3 treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular glutathione and MRP levels are reported with their relationship to ATO-resistance. 10, 14 Walter et al 15 reported that MRP1 might attenuate the susceptibility to GO, although by a smaller degree than P-gp. We could not find an obvious relationship between MRP1 and GO-resistance.…”
Section: Discussionmentioning
confidence: 99%